O storify e o jornalismo cidadão na internet - Seridório, Daniele Ferreira [UNESP]; Luvizotto, Caroline Kraus [UNESP] (Associacao Prudentina de Educacao e Cultura (APEC), 2014)
This study aims to understand the democratic and social potential of online citizen journalism, and how Storify can be use as a tool to achieve this goal. The focus is to analyse the use of this tool by media companies to verify if there are plurality of themes, or if there are gatekeeping of the information - such as occur in traditional media. The research will use the content analyse methodology to observe how three media companies use the website Storify: O Estado de São Paulo, Zero Hora and Veja. The results are based on the most frequent themes, which were divided into seven categories: police; politics; city; sport; technology; science and media. With this analyse we were able to concluded that, according to the theme, O Estado de Sao Paulo had, between the media companies analysed, the most plural approach, after it is Zero Hora, and lastly Veja.

Este estudo pretende compreender os potenciais democráticos e sociais do jornalismo cidadão na internet e como o Storify pode servir de ferramenta para atingir este fim. O problema concentrase em analisar o uso desta ferramenta por empresas de mídia para verificar a efetiva pluralidade das temáticas ou somente um reforço do agendamento que já ocorre nas versões tradicionais da notícia. A pesquisa utiliza a metodologia de análise de conteúdo para observar como três empresas midiáticas utilizam o Storify: jornal O Estado de São Paulo, jornal Zero Hora e revista Veja. Os resultados baseiam-se nas temáticas mais recorrentes que foram dividas em sete categorias: polícia; política; cidade; esporte; tecnologia; ciência e mídia. Esta análise permitiu concluir que em relação à temática o jornal O Estado de São Paulo foi, entre os veículos analisados, o mais plural, depois o jornal Zero Hora, e por fim, a revista Veja.
Storify and online citizen journalism
Keywords: Citizen journalism; Internet; Storify; Collective intelligence; Jornalismo cidadão; Internet; Storify; Inteligência coletiva